PENGARUH HARGA DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN TEH CELUP SARIWANGI (Studi Kasus di Retail Kota Palembang) - Sari, Dewi Purnama; Naruliza, Esty (Jemasi: Jurnal Ekonomi Manajemen dan Akuntansi, 2019)
Unilever Indonesia produces a variety of products, one of which is SariWangi Teabag. To stay afloat in the competition of SariWangi Teabag must continue to innovate starting in terms of price and product quality. Price is a monetary unit that is exchanged in order to obtain ownership rights or use of an item or service, and Product quality is a necessity that must be maintained and improved if a company wants to exist in sales competition. This research was made to analyze the effect of price and product quality on purchasing decisions partially and simultaneously. This study uses multiple linear regression analysis. In this study the population is infinite. The sampling method used is accidental sampling.The data used are primary data by distributing questionnaires directly to consumers of SariWangi Teabag in Palembang City Retail. The sample used was 272 respondents. The test is done in three stages, namely validity and reliability, classic assumption and hypothesis testing. The results of this study indicate that the coefficient of determination (R2) is 0.505 or 50.5% and the remaining 49.5% is influenced by other variables. The results of this study indicate that 50.5% of purchasing decisions can be explained by variable prices and product quality. Price variable (X1) is 38.6% and Product Quality variable (X2) is 11.9%.both partially and simultaneously Product Prices and Quality have a significant effect on purchasing.